Post-COVID-19 pandemic public health: Issues and challenges in India - Harshad Thakur (Wolters Kluwer Medknow Publications, 2022)
COVID-19 was an unexpected public health emergency. The key positive features of the Indian health system were demonstrated during the pandemic. Postpandemic is the time to introspect. Various issues and challenges facing the Indian Public Health System require due attention.